Final Report : Beyond Numbers : Valuing Quality Teaching in Business Education. - Kent, Jenny; Rohde, Fiona; Kavanagh, Marie; Mitchell, Graeme; Tennent, Beth; Horton, Chris (Australian Learning and Teaching Council (ALTC), 2011)
Final report from a project that considered how to identify, assess, support, recognise and value quality teaching within business faculties in an educationally meaningful and professionally relevant manner. Focus groups facilitated exploration of how quality teaching is perceived by staff and students to be measured, recognised and valued in the participating universities. Student responses presented relatively consistent perspectives, however the staff groups highlighted the need for staff experiences of valuing teaching to be contextualised within institutional cultures, policies and practices. The project provided an opportunity to develop and trial systems and processes that would support quality teaching and increase academic recognition of the need for and benefits from developing teaching capacity and leadership. Outcomes of the project included identification of: indicators of quality teaching that go beyond the metrics; processes and procedures for greater recognition of quality teaching; seed measures, including leadership approaches, that could be used to help gain momentum for the project outcomes beyond the teaching and learning enthusiasts; and 'tools' (including mid-session survey forms; student feedback focus group and peer observation guidelines and protocols; and awards criteria) which are available to other individuals and institutions to facilitate implementation of the successful strategies identified in this project.